A sequential methods study describing the perceptions of environmental barriers and the employment of persons with disabilities on a private healthcare company - Strydom, Nina (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScMedSc)--Stellenbosch University, 2013.